Chemical and physical soil attributes in integrated crop-livestock system under no-tillage - Silva, Hernani; de Moraes, Anibal; Carvalho, Paulo César; Fonseca, Adriel; Caires, Eduardo; Dias, Carlos Tadeu (Revista Ciência Agronômica, 2014)
Although integrated crop-livestock system (ICLS) under no-tillage (NT) is an attractive practice for intensify agricultural production, little regional information is available on the effects of animal grazing and trampling, particularly dairy heifers, on the soil chemical and physical attributes. The objective of this study was to evaluate the effects of animal grazing on the chemical and physical attributes of the soil after 21 months of ICLS under NT in a succession of annual winter pastures (2008), soybeans (2008/2009), annual winter pastures (2009), and maize (2009/10). The experiment was performed in the municipality of Castro (PR) in a dystrophic Humic Rhodic Hapludox with a clay texture. The treatments included a combination of two pasture (annual ryegrass monoculture and multicropping - annual ryegrass, black oat, white clover and red clover) with animal grazing during the fall-winter period with two animal weight categories (light and heavy), in a completely randomized block experimental design with 12 replications. After the maize harvest (21 months after beginning), soil samples were collected at 0-10 and 10-20 cm layers to measure soil chemical and physical attributes. The different combinations of pasture and animal weight did not alter the total organic carbon and nitrogen in the soil, but they influence the attributes of soil acidity and exchangeable cations. The monoculture pasture of ryegrass showed greater soil acidification process compared to the multicropping pasture. When using heavier animals, the multicropping pasture showed lesser increase in soil bulk density and greater macroporosity.